Prevalence and influencing factors of kinesiophobia after total knee arthroplasty: a systematic review and meta-analysis - Xingbin Du; Yuanwei Shao; Jian Xue; Jianda Kong (Journal of Orthopaedic Surgery and Research)
Abstract Background Knee osteoarthritis is a common degenerative disease in the elderly, and total knee arthroplasty is an effective treatment for end-stage knee joint diseases. However, kinesiophobia after surgery can impede patients’ rehabilitation and affect the recovery of knee joint function. There are differences in the research on its related influencing factors. Objectives This meta-analysis examined the prevalence and risk factors of kinesiophobia after TKA. Methods Pubmed, The Cochrane Library, China National Knowledge Infrastructure (CNKI), Embase, Web of Science on the prevalence and risk factors of kinesiophobia after TKA was searched in science, MEDLINE and other databases. Duplicate literature, low quality literature, literature with inconsistent observation indicators, and literature without full text were excluded. Two independent researchers used Newcastle-Ottawa Scale (NOS) to evaluate the quality of the included literature. After data extraction, Meta-analysis was performed using Stata17.0. Results A total of 11 articles involving 4039 cases were included in this meta-analysis to assess the prevalence of kinesiophobia after TKA. The overall prevalence was found to be 35% (95% CI: 27-44%). Subgroup analyses revealed varying prevalence rates based on age, education, income, and residence, with the highest prevalence observed in individuals under 65 years and those with lower levels of education and income. Key factors influencing the prevalence of kinesiophobia included pain (OR = 2.313, 95% CI: 1.556–3.07), low social support (OR = 1.681, 95% CI: 1.000-2.361), and negative coping strategies (OR = 1.344, 95% CI: 1.165–1.523). Conclusion The prevalence of kinesiophobia after TKA is high. There are differences in the prevalence of kinesiophobia among people with different places of residence, different education levels, and different monthly incomes. At the same time, it is affected by many factors such as postoperative pain, low social support, low self-efficacy, negative coping, old age, and low education level.